Cervico-cephalalgiaphobia: a subtype of phobia in patients with cervicogenic headache and neck pain? A pilot study. (7th August 2016) - Oostendorp, Rob A. B.; Elvers, Hans; Mikolajewska, Emilia; Roussel, Nathalie; van Trijffel, Emiel; Samwel, Han; Nijs, Jo; Duquet, William
Abstract : Objectives: The term 'cephalalgiaphobia' was introduced in the mid-1980s and defined as fear of migraine (attacks). We hypothesized that a specific subtype of cephalalgiaphobia affects patients with cervicogenic headache (CEH). This study aimed to: (1) define the term 'cervico-cephalalgiaphobia'; (2) develop a set of indicators for phobia relevant to patients with CEH; and (3) apply this set to a practice test in order to estimate the frequency of cervico-cephalalgiaphobia in the Dutch primary care practice of manual physical therapy. Methods: A systematic approach was used to develop a definition and potential indicators for cervico-cephalalgiaphobia. An expert group appraised the definition and the set of indicators (score per indicator: never; sometimes; often/always). An invitation to participate in the practice test was sent to Dutch manual physical therapy practices ( n  = 56) representing 134 manual physical therapists (MPTs). The cut-off point for percentages of scores for coverage of the indicators was set at ≥ 60%. Results: The expert group agreed with the proposed definition of cervico-cephalalgiaphobia. A set of eight indicators for cervico-cephalalgiaphobia was selected from 10 initial indicators. Thirty-six MPTs provided data from 46 patients diagnosed with CEH. The coverage of 'often/always' was substantial for the indicators, 'Short-term positive results in previous manual physical therapeutic treatment', 'Shorter interval between treatment sessions', 'Fear of "locked facet joints" of the neck', 'More frequent manipulation', and 'Fear of increase in headaches'. Coverage was also substantial for 'never' regarding 'Long-term positive results in previous manual physical therapeutic treatment'. 'Confirmation of "locked facet joints" of the cervical spine by MPT as a cause for increase of CEH' scored 'often/always' in all patients. Coverage for 'Increased use of medication with insufficient effect' was substantial, scoring as 'sometimes' in 39 (84.8%) patients. Discussion: Cervico-cephalalgiaphobia was defined and a set of eight indicators formulated based on the literature and clinical expertise. The practice test provides valuable information on the frequency of indicators for cervico-cephalalgiaphobia in the Dutch manual physical therapy practice, suggesting that cervico-cephalalgiaphobia is common in patients with CEH.